Comprehensive Analysis of Sustainability Rating Systems for Road Infrastructure - Rajab Ali Mehraban; Lucia Tsantilis; Pier Paolo Riviera; Ezio Santagata (Infrastructures)
Sustainability rating systems (SRSs) have emerged as indispensable frameworks for advancing the environmental, social, and economic sustainability of road infrastructure. Despite their growing adoption, their integration as authoritative tools within infrastructure planning and development remains limited. This study provides a comprehensive evaluation of eight leading SRSs—CEEQUAL, Greenroads, GreenLITES, GreenPave, I-LAST, INVEST, BE2ST-in-Highways, and Envision—focusing on their structural frameworks, criteria weightings, adherence to the three pillars of sustainability, and alignment with international benchmarks such as ISO, EN, and ASTM standards. By considering the three pillars of sustainability, the analysis of the eight SRSs reveals a disproportionate focus on environmental well-being (43%) and social well-being (42%), with economic well-being receiving minimal emphasis (15%). Furthermore, this study identifies notable deficiencies in the integration of critical international standards, including ISO, EN, and ASTM, which constrains the comprehensiveness and global applicability of these frameworks. Key findings suggest that the current SRSs inadequately address the principles of a circular economy, risk management, and social equity, highlighting areas for methodological enhancement. This review offers critical insights for researchers, policy makers, and practitioners seeking to refine sustainability rating systems for road infrastructure. By consolidating existing knowledge and proposing methodological advancements, this study contributes to the evolution of SRSs into comprehensive, globally relevant tools for sustainable infrastructure development.